4-Bromodiphenyl ether delays pubertal Leydig cell development in rats. (November 2018) - Chen, Xianwu; Dong, Yaoyao; Tian, Erpo; Xie, Lubin; Wang, Guimin; Li, Xiaoheng; Chen, Xiuxiu; Chen, Yong; Lv, Yao; Ni, Chaobo; Fang, Yinghui; Zhong, Ying; et al.
Abstract: Polybrominated diphenyl ethers are a class of brominated flame retardants that are potential endocrine disruptors. 4-Bromodiphenyl ether (BDE-3) is the most abundant photodegradation product of higher polybrominated diphenyl ethers. However, whether BDE-3 affects Leydig cell development during puberty is still unknown. The objective of this study was to explore effects of BDE-3 on the pubertal development of rat Leydig cells. Male Sprague Dawley rats (35 days of age) were gavaged daily with BDE-3 (0, 50, 100, and 200 mg/kg body weight/day) for 21 days. BDE-3 decreased serum testosterone levels (1.099 ± 0.412 ng/ml at a dose of 200 mg/kg BDE-3 when compared to the control level (2.402 ± 0.184 ng/ml, mean ± S.E.). BDE-3 decreased Leydig cell size and cytoplasmic size at a dose of 200 mg/kg, decreased Lhcgr, Star, Dhh, and Sox9 mRNA levels at ≥ 100 mg/kg and Scarb1, Cyp11a1, Hsd17b3, and Fshr at 200 mg/kg. BED-3 also decreased the phosphorylation of AKT1, AKT2, ERK1/2, and AMPK at 100 or 200 mg/kg. BDE-3 in vitro induced ROS generation, inhibited androgen production, down-regulated Lhcgr, Scarb1, Star, Cyp11a1, Hsd3b1, Srd5a1, and Akr1c14 expression in immature Leydig cells after 24-h treatment. In conclusion, the current study indicates that BDE-3 disrupts Leydig cell development via suppressing AKT, ERK1/2, and AMPK phosphorylation and inducing ROS generation. Graphical abstract: Image 1 Highlights: 4-Bromodiphenyl ether delays pubertal Leydig cell development. 4-Bromodiphenyl ether down-regulates Leydig cell gene expression. 4-Bromodiphenyl ether blocks Leydig cell some kinase phosphorylation. 4-Bromodiphenyl ether induces Leydig cell ROS generation.